EXAMINING THE INDIGENIOUS WISDOM IN EKEGUSII PROVERBS (The University of Nairobi Journal of Language and Linguistics, 2023)
This paper examines the cultural values and wisdom that aretransmitted through Ekegusii proverbs. It demonstrates how proverbsare used to comment on a variety of human experiences and tomaintain societal order. Some of the cultural issues that the paperexamines include gender construction, paradoxical experiences, as wellas the perception of death. The paper further shows that even ininstances where the proverbs appear contradictory, there aresociological reasons to explain and unravel the apparent incongruity. Inaddition, the paper reveals the existence of synonymous proverbs whichare a result of cultural contact, arising mainly from the translation (intoEkegusii) of English and Kiswahili expressions.